Effect of Royal Palm (Roystonea regia) nut meal intake on serum biochemical indices of broilers chickens - Martínez-Pérez, Madeleidy; Vives-Hernández, Yesenia; Rodríguez-Sánchez, Bárbara; Alcivar-Cobeña, José (Revista Científica de la Facultad de Ciencias Veterinarias, 2022)
The experiment was carried out with the objective of studying the effect of royal palm -RP- (Roystonea regia) fruit meal intake on serum biochemical indices of broilers (B). An amount of 32 male animals from eight to 42 days of age were used, which were distributed according to a completely randomized design in four treatments (T) and eight repetitions: control (corn-soybean) and the inclusion of RP nut meal at 5, 10 and 15%. Body weight (BW), digestive indicators and serum biochemical indices related to protein, carbohydrate, lipid and mineral metabolism, as well as liver function were determined. BW was higher in birds that consume 15% RP nut meal compared to the rest of T. An increase in total proteins and uric acid was observed in the treatments where the RP fruit was included compared to the control (29.86 vs 34.78; 34.78 and 37.34 grams·liters-1 [L-1]; 252.75 vs 310.63; 278.88 and 303.13 Micromol·L-1), respectively. Triglycerides decreased with the presence of non-traditional feed (1.49 vs 1.00; 1.06 and 1.06 Milimol·L-1) while cholesterol only decreased with 5% inclusion. No differences were observed between T for indicators of carbohydrate and mineral metabolism. There was no damage to liver function at the levels tested. It was concluded that the consumption of RP nut meal by B up to 15% modifies indicators of blood biochemistry related to protein and lipid metabolism and no signs of liver damage are shown.